The Production of Vacancies During Reversed Plastic Flow - Jaffrey, Donald (My University, 1966)
The Portevin-le Chatelier effect in a copper-3.2 at.% tin alloy has been used to investigate the rate of vacancy production during reversed plastic flow. The production rate per unit strain has been shown to be approximately half the value found for straight tensile deformation. It was inferred from this that fatigue is not a highly efficient method for producing vacancies. The relationship between the dislocation density and the tensile plastic strain for this alloy has been determined by transmission electron microscopy. It was found to obey the law, p = const. E^1.17±0.13. It was also found that during reversed plastic flow this law was no longer valid.
Keywords: production of vacancies; reversed plastic flow; plastic flow; vacancies during reversed plastic flow; metallurgy